Gastric Mucormycosis in a Renal Transplant Patient Treated with Isavuconazole Monotherapy - Imran Gani; Atbin Doroodchi; Kristina Falkenstrom; Holly Berry; Won Lee; Laura Mulloy; Muhammad Saeed; Rajan Kapoor (Case Reports in Transplantation)
Gastrointestinal mucormycosis is a rare infection in solid organ transplant recipients. Our patient, a 79-year-old male, presented with severe dysphagia and odynophagia about 2 weeks after receiving a renal transplant. An upper gastrointestinal (UGI) endoscopy revealed esophagitis and gastric ulceration, the cultures from which grew Rhizopus species. A usual treatment strategy should include Amphotericin B as monotherapy or in combination with Posaconazole or Isavuconazole for such infections. Our patient was treated with Isavuconazole monotherapy, in an effort to minimize renal toxicity from Amphotericin B to the new allograft. Unique to our case was a successful clinical response and resolution of UGI lesions with Isavuconazole monotherapy. Due to the vagueness of presenting symptoms, such infections can be easily missed in an immunocompromised patient which can have tragic outcomes. Prompt diagnosis and modulation of immunosuppression are essential to decrease mortality and morbidity. Isavuconazole is a novel agent and can be used as a monotherapy for such infections, especially in renal transplant recipients.